Research progress on Cornus officinalis and its active compounds in the treatment of diabetic nephropathy - Wu, Chenguang; Wang, Jingjing; Zhang, Rui; Zhao, Hailing; Li, Xin; Wang, Lifan; Liu, Peng; Li, Ping (Frontiers in Pharmacology, 2023)
Diabetic nephropathy (DN) is a kidney disorder secondary to diabetes and is one of the main diabetic microvascular complications. As the number of diabetic patients grows, DN has become the leading cause of chronic kidney disease in China. Unfortunately, no definitive cure currently exists for DN. Cornus officinalis (CO), frequently utilized in clinical settings for diabetes mellitus treatment, has proven vital in both preventing and treating DN. This article explores the pathogenesis of DN and how CO and its active compounds regulate glucose and lipid metabolism, exhibit anti-inflammatory properties, inhibit oxidative stress, regulate podocytes, and manage autophagy. The mechanism and role of and its active compounds in the treatment of DN are discussed.